Od rekreacji do e-sportowej profesjonalizacji. Kulturowo-społeczne aspekty gier elektronicznych = From recreation to e-sports professionalization. Cultural and social aspects of electronic games - Sahaj, Tomasz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this article is to present the dynamically developing phenomenon of gaming against the background of the broader social reality. Electronic games (computer games, console games, etc.) are a phenomenon of contemporary digital culture, which allow players to interact in the real and virtual worlds. Such games are used for more than just entertainment: they are part of practical applications used in medicine and rehabilitation, recreation and sport. E-sports is an expression of global trends. It is also a simulacrum of traditional sport, which imitates it in many respects but also establishes new social relationships. E-sports is slowly making its way into secondary and higher education, emerging as an integral component of modern physical education and professional sport.
Keywords: gry elektroniczne; e-sport; kultura; społeczeństwo; electronic games; e-sports; culture; society